Stroke Treatment With PAR-1 Agents to Decrease Hemorrhagic Transformation - Lyden, Patrick D.; Pryor, Kent E.; Minigh, Jennifer; Davis, Thomas P.; Griffin, John H.; Levy, Howard; Zlokovic, Berislav V. (Frontiers in Neurology, 2021)
Ischemic stroke is a leading cause of death and the most widespread cause of disability in industrialized nations. Currently, the most commonly used approved treatment for acute stroke is recanalization therapy with thrombolytic drugs such as tissue plasminogen activator (rt-PA or tPA) or endovascular mechanical thrombectomy. Although tPA and thrombectomy are widely available in the United States, it is estimated that only 10% to 20% of stroke patients receive recanalization treatment, in part due to restrictive selection criteria. Recently, however, tPA and thrombectomy selection criteria have loosened, potentially allowing more patients to qualify. The relatively low rate of treatment may also reflect the perceived risk of brain hemorrhage following treatment with tPA. Adjunctive therapies given along with thrombolysis and thrombectomy may reduce hemorrhagic transformation after recanalization. Such adjuncts may likely enhance the availability of recanalization and encourage more physicians to use the recently expanded selection criteria for applying recanalization therapies. This article presents a discussion of stroke therapies, the role of hemorrhagic transformation in producing poor outcomes, and an activated protein C (APC)-based approach that is showing promise for decreasing hemorrhagic transformation and improving outcomes.